EFEKTIFITAS MEDIA ALAM DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) DI SEKOLAH ALAM UNGARAN (SAUNG) KABUPATEN SEMARANG - Baen, Faldin (Al-Fikri: Jurnal Studi dan Penelitian Pendidikan Islam, 2019)
ABSTRACTThis study aims to describe the natural media in learning Islamic religious education (PAI) in SAUNG. In addition, this research was also conducted to explain the effectiveness of natural media in learning Islamic religious education at SAUNG schools. The focus of the problem in this study included: (1) Utilization of natural media in the learning of Islamic religious education (PAI) at the ungaran (SAUNG) natural school, (2) Effectiveness of natural media in learning Islamic education (PAI). This research uses descriptive analytical method with data collection techniques in the form of interviews, observation and documentation. Data that has been collected will be analyzed by means of data reduction, data presentation and conclusion drawing. From the results of research in the field it was found that the utilization of natural media is done by applying the learning tools implemented under the program MABIT, outting, outbound, cooking and gardening. The effectiveness of natural media in teaching Islamic religious education (PAI) in nature school Ungaran (SAUNG) managed to make children feel comfortable to learn PAI and produce good cognitive value. The conclusion of the study was the use of natural media in teaching Islamic religious education (PAI) in nature school Ungaran (SAUNG) is done in some programs, namely MABIT, outting, outbound, cooking and gardening. This makes children feel comfortable in the study of Islamic religious education (PAI) and managed to increase the value of cognition in children.Â Key Words: Natural Media, Islamic Religious Education, Natural School of Ungaran (SAUNG)